Las esculturas de la ciudad. Un programa de memoria nacional en Bogotá, 1880-1910 (Estudios) - Mejía Pavony, Germán Rodrigo (2020)
The article examines how frameworks for national memory were installed in Bogotá between the end of the nineteenth century and the early twentieth century. Although there was already a state-run program of sculptures being implemented in the Cementerio de la Ciudad (municipal cemetery), up to 1870 there was a deliberate action to transform public spaces into a script of the “country’s history,” including the naming of streets, changing the colonial names of public squares, the emergence of “gardens of the republic,” and the placement of statues in various locations. While the city was becoming a political hub for the nation, urban spaces were being remodeled to support its collective memory.